PESANTREN ECOLOGY MODEL: INTEGRATION OF FIQH AL-BI'AH, ECOOSOPHY, AND LOCAL WISDOM AT NURIS ISLAMIC BOARDING SCHOOL JEMBER - Mustakim, Adam (Universitas Dharmawangsa, 2025)
This study aims to reveal the philosophical foundations, environmental management practices, and the process of internalizing ecological values at the Nurul Islam Islamic Boarding School (Nuris) Jember in building an ecological model of pesantren based on fiqh al-bi'ah, ecosophism, and local wisdom. This research uses a qualitative approach with a case study type. Data was collected through observations, in-depth interviews with kiai, ustadz, pesantren administrators, and senior students, as well as documentation of pesantren environmental activities and policies. Data analysis uses an interactive analysis model that includes data reduction, data presentation, and conclusion drawn. The results of this study reveal three main findings. First, the philosophical foundation of the ecological movement at the Nuris Islamic Boarding School is rooted in the value of ecological monotheism, the mandate of the caliphate, and the prohibition of isrāf which is internalized through the teaching of the book, example, and habituation. Second, environmental management practices run through waste sorting, eco-enzyme programs, simple waste treatment, and student innovation through scientific activities. Third, the internalization of ecological awareness is formed through the local wisdom of pesantren in the form of communal discipline, a common living system, hygiene rules, and a culture of mutual cooperation that strengthens the ecological behavior of students. These findings show that the ecological model of pesantren can be built through the integration of Islamic values, ecosophism, and local culture in pesantren education